3 - Public Spheres, Personal Papers, Pedagogical Practices: Ruth First’s Academic Postings to/ from Dar es Salaam and Maputo: https://doi.org/10.4314/ad.v35i4.70216 - Harlow, Barbara (Africa Development, 2021)
This article proposes to consider, in particular, Ruth First’s work in her final years at the University of Dar es Salaam (Tanzania) and Universidade Eduardo Mondlane, Maputo, Mozambique (UEM), with reference to her own biographical trajectory and towards a reconsideration of contemporary and subsequent developments in the institutional history of post-independence education: public spheres (the university), personal papers (the archive), and pedagogical practices (the classroom).